Protease and Phytohormone Production by Potassium solubilizers Isolated from Maize Rhizosphere - Nwokeh, Uchenna Jonathan; Soretire, Adeniyi Adebowale; Babalola, Oluwatoyin Abimbola; Akintokun, Aderonke Kofoworola (Direct Research Journal of Agriculture and Food Science, 2024)
Enzymes and phytohormones are essential substances required for plant development, especially at their vegetative stage. Microbial-plant-root interactions on rhizosphere region make possible for both nutrient mineralization and absorption. An in-vitro assessment was carried out to assess the protease, indole acetic and gibberellic acids production patterns by Lysinibacillus fusiformis and Providencia rettgeri. Both bacterial strains produced indole acetic and gibberellic acids; two essential phytohormones necessary for seed germination and fruit ripening. Time of incubation of both bacterial inoculants had significant effects (p<0.05) on protease activities. Lysinibacillus fusiformis produced more protease (0.6630±0.003 µg/mL) at 96 h after incubation, while the highest protease activity by Providencia rettgeri was observed at 72 h after incubation with a mean value of 0.4605±0.004 µg/mL. However, Lysinibacillus fusiformis produced more protease enzyme compared to Providencia rettgeri. The production trends of gibberellic and indole acetic acids were also study. The amount of gibberellic acid produced changed significantly (p<0.05) with time. The activity of gibberellic acid was at its peak 48 h after incubation for both Lysinibacillus fusiformis (76.25±0.21 µg/mL) and Providencia rettgeri (151.85±0.78 µg/mL), with Providencia rettgeri producing more gibberellic acid than Lysinibacillus fusiformis. The highest production of IAA was at its peak at 72 h after incubation for Lysinibacillus fusiformis (1.4530±0.001 µg/mL) but was not significantly (p>0.05) different with change in time. Providencia rettgeri produced more IAA at 72 h of incubation (1.1450±0.004 µg/mL) and was significantly (p<0.05) different with change in time.